Ответ(ы) на вопрос:
Гость
Найдем первую производную
[latex](x+cos \frac{1}{x^2})' = (x)'+(cos \frac{1}{x^2})'=1-sin\frac{1}{x^2}*(-2x^{-3})=[/latex]
[latex]= 1+(2x^{-3})*sin\frac{1}{x^2}[/latex]
Найдем вторую производную
[latex](1+(2x^{-3})*sin\frac{1}{x^2})' = (1)'+((2x^{-3})*sin\frac{1}{x^2})' = ((2x^{-3})*sin\frac{1}{x^2})'=[/latex]
[latex]= (2x^{-3})'*sin\frac{1}{x^2} + (2x^{-3})* (sin\frac{1}{x^2})'=[/latex]
[latex]= -6x^{-4} * sin\frac{1}{x^2} + 2x^{-3}* cos\frac{1}{x^2}*(-2x^{-3}) =[/latex]
[latex]= -6x^{-4} * sin\frac{1}{x^2} - 4x^{-6}* cos\frac{1}{x^2} [/latex]
Не нашли ответ?
Похожие вопросы